Meta-Analysis of the Effect of Prenatal Stress on the Premature Birth - Faujiah, Irfa Nur; Murti, Bhisma; Prasetya, Hanung (Journal of Maternal and Child Health, 2020)
Background: Premature birth is a major global public health problem, especially in developing countries. One of the causes of this incident is exposure to psychological stress experienced during pregnancy. This study aims to estimate the magnitude of the effect of prenatal stress on preterm birth using a meta-analysis study.Subjects and Method: The meta-analysis research was conducted by selecting articles published in the years 2006-2020, from the PubMed, Google Scholar, Science Direct, Direc